THE ROLE OF UNASUR IN INTRA-STATE CONFLICTS IN THE REGION - ALEJANDRO AMIGO TOSSI (Política y Estrategia, 2017)
The UNASUR treaty does not consider the prevention of conflicts, however, one of its objectives is to create an area of peace in South America, and for that purpose, has intervened in a series of conflicts that have threatened the stability of the region. The cases have gone from the stabilization of an inter-state crisis to an unsuccessful attempt to stop a president’s impeachment. This article describes the circumstances that shaped the internal conflicts of Bolivia in 2008, Ecuador in 2010 and Paraguay in 2012; and the subsequent role of UNASUR in those intra-state situations.